Real-Time Landslide Forecasting System: An Application of IoT Technology - Nguyen, Duc-Nghiem; Nguyen, Viet-Phuong (International Journal of Sustainable Construction Engineering and Technology, 2022)
Under the effects of climate change, especially the increase in rainfall intensity, the landslide has recently made a lot of consequences. Therefore, slope failure forecasting has been viewed as a key task to save human lives and economic losses. In the past, slope monitoring was often carried out manually directly on-site, therefore very difficult to get data continuously for a long time, with a too low temporal frequency that does not permit precise forecast. Recently, applying IoT (Internet of Things) technology in monitoring has begun popular. This technology allows data can be automatically gathered, updated and transmitted via the internet in real-time. This not only permits a more precise forecast but also prompt responses before the failure really happen. This paper introduces an IoT integrated model for forecasting the time of failure based on displacements. The detailed guidelines of theoretical basis, how to install devices and how to collect, process and transmit data are represented, so this would be easy and convenient to apply in practice. A small-scale physical model was made to test the function of the system. The simulation tests indicated good performance.